Amitraz poisoning: a case report. - Choor, CK; Santha, KN (Penerbit UKM, 2011)
Amitraz poisoning is rare and there has been no reported cases in the Malaysian literature. Ingestion of this compound carries many life threatening side effects. We describe a case of Amitraz poisoning in an 18 years old young adult. He developed hypotension, required ventilatory support and a day of intensive care unit stay. He had a quick recovery after he was treated symptomatically and was discharged well after 3 days.